Pengaruh Marketing Public Relations Terhadap Brand Awareness Cyto Apparel Melalui Media Sosial - Ayubi, Salahudin; Vaala, Aqi; Rahmawati, Alfiah Arnel; Fariha, Naela Faza (CV. ITTC INDONESIA, 2024)
The increasing development of the clothing business world and the digitalization of marketing provide opportunities for MSMEs to create creativity and innovation in their products. One of the things done by the sportswear brand Cyto Apparel is implementing marketing public relations through social media as a marketing effort to increase brand awareness. Therefore, this research was conducted to examine the relationship between marketing public relations and Cyto Apparel brand awareness through social media. The research method uses quantitative by collecting questionnaire data. The sample from this research was 100 sports fans within the Special Region of Yogyakarta. Data analysis used the Statistical Package for the Social Sciences (SPSS) software. The research results show that marketing public relations has a significant effect on social media and brand awareness of Cyto Apparel. Social media also acts as an intervening variable between marketing public relations and Cyto Apparel brand awareness..